2020
DOI: 10.1371/journal.pmed.1003296
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced treatment strategies and distinct disease outcomes among autoantibody-positive and -negative rheumatoid arthritis patients over 25 years: A longitudinal cohort study in the Netherlands

Abstract: Background Based on different genetic and environmental risk factors and histology, it has been proposed that rheumatoid arthritis (RA) consists of 2 types: autoantibody-positive and autoantibody-negative RA. However, until now, this remained hypothetical. To assess this hypothesis, we studied whether the long-term outcomes differed for these 2 groups of RA patients. Methods and findings In the Leiden Early Arthritis Clinic cohort, 1,285 consecutive RA patients were included between 1993 and 2016 and followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 44 publications
1
42
0
3
Order By: Relevance
“…Previous literature already showed that the presence of autoantibodies in RA is associated with a worse treatment response and outcome. Moreover, autoantibody-negative RA patients have a better treatment response compared to autoantibody-positive RA patients when given similar therapies [ 21 ]. In accordance with previous literature, we found a shortened biological survival due to inefficacy or adverse events in RF-positive RA patients but also the inability to taper TNF inhibitors after reaching remission in ACPA-positive RA patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature already showed that the presence of autoantibodies in RA is associated with a worse treatment response and outcome. Moreover, autoantibody-negative RA patients have a better treatment response compared to autoantibody-positive RA patients when given similar therapies [ 21 ]. In accordance with previous literature, we found a shortened biological survival due to inefficacy or adverse events in RF-positive RA patients but also the inability to taper TNF inhibitors after reaching remission in ACPA-positive RA patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early (rheumatoid) arthritis can be divided into the following three clinical phenotypes: undifferentiated arthritis (UA), autoantibody (ACPA and RF) negative RA (RA−) and autoantibody positive RA (RA+). 6 14 UA refers to patients with arthritis who do not meet the 2010 and 1987 classification criteria for RA, which corresponds with the patients with early arthritis described in the EULAR recommendations for early arthritis. 15 16 Patients with RA do fulfil either the 2010 or 1987 classification criteria for RA.…”
Section: Clinical Phenotypes Of Early (Rheumatoid) Arthritismentioning
confidence: 99%
“… 16 The subdivision of these phenotypes was originally based on differences in (progression of) erosive disease, while nowadays only DMARD-free remission (DFR) rates and the number of treatment intensifications needed to reach remission differ. 6 13 14 On the other hand, all clinical phenotypes have a similar impact on patients’ lives when patient-reported outcomes are compared. 14 From a pathophysiological point of view, genetic as well as environmental risk factors differ between RA+ and RA−.…”
Section: Clinical Phenotypes Of Early (Rheumatoid) Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…8 Equally important, despite the incidence of autoantibody-negative RA is increasing, 4 restrictions imposed by the pandemic, together with the erroneous but common beliefs attributing to this disease subtype a harmless course, may leave patients with less abrupt onsets underdiagnosed, with further impact on prognosis which remains per se unfavourable even in the modern treatment era. 7 The challenge is thus to keep on fighting COVID-19 without forgetting non-COVID-19 diseases.…”
mentioning
confidence: 99%